1983
DOI: 10.1111/j.1570-7458.1983.tb03317.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF INTENSITY AND DURATION OF LOW TEMPERATURES IN REGULATING DIAPAUSE DEVELOPMENT OF THE CABBAGE ROOT FLY (DELIA RADICUM)

Abstract: Low temperature was shown to be the major factor regulating diapause development of the cabbage root fly. Diapausing pupae had to be subjected to temperatures of from 0°—6° for 22 weeks for all individuals in the population to complete diapause development. Once this was complete, pupae required a further 14 days at 20° for most of the flies to emerge. Flies that emerged within 14 days at 20°, the criterion for diapause completion, were classed as early‐emerging. The percentage of early‐emerging flies graduall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…Diapausing pupae were then collected from the rutabaga, stored at 4°C and a photoperiod of 8:16 (L:D)h for a minimum of 16 wk to complete diapause development, and then placed at 20°C and a photoperiod of 16:8(L:D)h and fly emergence recorded daily. Although Collier & Finch (1983) reported that 20 wk was necessary for completion of diapause development for D. radicum populations in England, flies emerged from 80% of pupae collected in our studies, indicating that our population required a shorter cold treatment than the Collier & Finch (1983) population for completion of diapause development.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…Diapausing pupae were then collected from the rutabaga, stored at 4°C and a photoperiod of 8:16 (L:D)h for a minimum of 16 wk to complete diapause development, and then placed at 20°C and a photoperiod of 16:8(L:D)h and fly emergence recorded daily. Although Collier & Finch (1983) reported that 20 wk was necessary for completion of diapause development for D. radicum populations in England, flies emerged from 80% of pupae collected in our studies, indicating that our population required a shorter cold treatment than the Collier & Finch (1983) population for completion of diapause development.…”
mentioning
confidence: 70%
“…In Finch & Collier's (1983) In view of the later emerging characteristics of progeny from the L x L crosses compared with all other crosses (Fig. 1), it seems possible that a late-emerging biotype could easily evolve from this intermediate biotype if early emergers were removed from the population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations